ANALISIS PERMINTAAN OBYEK WISATA MASJID AGUNG SEMARANG - Budi M, Arifta; Budi Santosa, Purbayu (Diponegoro Journal of Economics, 2013)
Great Mosque of Semarang attractions chosen because attraction is one of the attractions in the city of Semarang, who has the lowest number of visitors compared to the Great Mosque of Demak attraction but it has economic value. The purpose of this study was to determine whether the cost of a trip to the Grand Mosque of Semarang attractions, travel to other attractions (Demak), individual income, distance, time, age, amenities and beauty affect the number of requests to the attraction of the Great Mosque of Semarang, Semarang. The analytical tool used in this study is multiple linear regression with the number of visits as the dependent variable and eight independent variables. The results showed five variables affect the total demand of tourism to the Grand Mosque of Semarang is the cost of travel to get to the Grand Mosque of Semarang, distance, time, facilities and beauty. Variable distance regression coefficient produced a value of 0.093, this means an increase in distance will result in the number of requests under the assumption that the cost of a trip to the Grand Mosque of Semarang attractions, travel to other attractions (Great Mosque of Demak), individual income, time, age and previous experience of visiting the objec fixed (constant). It was concluded that the higher the previous visit experience, the higher the number of requests to the attraction of the Great Mosque of Semarang.